Ultrapure laser-synthesized Si nanoparticles with variable oxidation states for biomedical applications. Issue 48 (21st November 2016) - Al-Kattan, Ahmed; Ryabchikov, Yury V.; Baati, Tarek; Chirvony, Vladimir; Sánchez-Royo, Juan F.; Sentis, Marc; Braguer, Diane; Timoshenko, Victor Yu.; Estève, Marie-Anne; Kabashin, Andrei V.
Abstract : We use femtosecond laser fragmentation to fabricate ultrapure bare Si-based nanoparticles (Si-NPs) for biomedical applications. Abstract : We employ a method of femtosecond laser fragmentation of preliminarily prepared water-dispersed microcolloids to fabricate aqueous solutions of ultrapure bare Si-based nanoparticles (Si-NPs) and assess their potential for biomedical applications. The nanoparticles appear spherical in shape, with low size dispersion and a controllable mean size, from a few nm to several tens of nm, while a negative surface charge (−35 mV ± 0.10 according to z -potential data) provides good electrostatic stabilization of colloidal Si-NP solutions. Structural analysis shows that the Si-NPs are composed of Si nanocrystals with inclusions of silicon oxide species, covered by a SiO x (1 < x < 2) shell, while the total oxide content depends on whether the fragmentation is performed in normal oxygen-saturated water (oxygen-rich conditions) or in water deoxygenated by pumping with noble gases (Ag or He) before and during the experiment (oxygen-free conditions). Our dissolution tests show the excellent water-solubility of all the NPs, while more oxidized NPs demonstrate much faster dissolution kinetics, which is explained by oxidation-induced defects in the core of the Si-NPs. Finally, by examining the interaction of the NPs with human cells after 72 h of incubation at different concentrations, we report the absence of any adverse effects of the NPs up to high concentrations (50 μg mL −1 ) and a good internalization of NPs via a classical endocytosis mechanism. Possessing far superior purity compared to their chemically synthesized counterparts and enabling a variety of imaging and therapeutic functionalities, the laser-synthesized Si-NPs are promising for safe and efficient applications in nanomedicine.